Fantasi dan Ilusi: Interaksi Parasosial Fandom ARMY BTS di Media Sosial - Ananda Noviasyri (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2022)
This study examines ARMY BTS' parasocial interactions on social media as a result of being exposed to popular culture. Parasocial interaction refers to the relationship that develops between audiences and idolized figures through the media. This study uses a qualitative-descriptive method with the approach of Horton and Wohl's parasocial theory in a constructivist paradigm. By using in-depth interviews with three BTS ARMY informants, this study found that the presence of new media provides a more different character of parasocial interaction than the old media because fans can establish relationships with BTS as if they were conducting interpersonal communication without having to get attention. ARMY's parasocial interactions are already at the level of intense personal feeling, assuming that there is an emotional closeness between him and the character he idolizes. Apart from that, this behavior also makes ARMY always want to know the latest BTS information, establish social relations with fellow ARMYs, are willing to buy albums, merchandise or anything related to BTS, to do imitations such as following the fashion of BTS members.